THE IMPACT OF TACROLIMUS ON GROWTH FACTORS IN EXPERIMENTAL PROLIFERATIVE VITREORETINOPATHY - Turgut, Burak; Uyar, Fatma; Ustundag, Bilal; Celiker, Ulku; Akpolat, Nusret; Demir, Tamer (Lippincott Williams & Wilkins, 2012)
Purpose: To investigate the effect of intravitreal tacrolimus on an animal model of proliferative vitreoretinopathy (PVR) and on growth factors implicated in its pathogenesis. Methods: Twenty-one guinea pigs were randomly assigned to one of three groups of seven animals each: no-PVR/saline group (no PVR/intravitreal saline-injected group), PVR/saline group (dispase-induced PVR group, treated with control injections of intravitreal saline), and PVR/tacrolimus group (treatment group, dispase-induced PVR group treated with intravitreal tacrolimus injections). At the end of the experiment, eyes were enucleated and the identification of the stages of PVR was carried out. While a halves of the enucleated globes were evaluated histopathologically for PVR formation, the retinas of the other halves of globes were used for the preparation of retinal homogenates. The transforming growth factor-beta, platelet-derived growth factor, and fibroblast growth factor levels in homogenized retina tissues were measured by the enzyme-linked immunosorbent assay method. Results: When assessing the average PVR stages in terms of severe PVR rates, the PVR/tacrolimus group had significantly improved when compared with the PVR/saline group. The PVR/tacrolimus group demonstrated significantly decreased levels of transforming growth factor-beta, platelet-derived growth factor, and fibroblast growth factor when compared with the PVR/saline group and also demonstrated significant improvement in epiretinal membrane formation and retinal fold in the presence of histopathologic levels. The difference in degradation of photoreceptor cells between the PVR/tacrolimus and the PVR/saline groups was not statistically significant. Conclusion: This study suggests that intravitreal tacrolimus application may suppress PVR development and that tacrolimus may merit investigation for the prophylaxis of PVR. RETINA 32:232-241, 2012
Keywords: proliferative vitreoretinopathy; tacrolimus; transforming growth factor-beta; platelet-derived growth factor; fibroblast growth factor